Finiteness theorem for multi-K-bi-Lipschitz equivalence of map germs - Birbrair, Lev; Ferreira Costa, João Carlos [UNESP]; Da Silva Sena Filho, Edvalter; Mendes, Rodrigo (Wiley, 2018)
Let Pk(n,p) be the set of all real polynomial map germs f=(f1,...,fp):(Rn, 0)-> (Rp, 0) with degree of f1,...,fp less than or equal to k ∈ N. The main result of this paper shows that the set of equivalence classes of Pk(n,p), with respect to multi- k -bi-Lipschitz equivalence, is finite.
Keywords: bi-Lipschitz contact equivalence; finiteness theorem; Lipschitz classification